Lack of mate selectivity for genetic compatibility within the red brocket deer Mazama americana complex - Carranza, Juan; Roldán, Mar; Duarte, José Maurício Barbanti (Springer Nature, 2017)
Red brocket deer Mazama americana includes at least two lineages that differ at the level of karyotypes and phylogenetic relationships based on mtDNA. Also, hybrids between them have been proved to be nonviable or infertile. Since successful breeding is hampered, we expect selection to have produced a precopulatory barrier between these lineages based on courtship behaviour, to prevent investment in unsuccessful breeding. Here we made experiments with specimens in captivity to investigate mating preferences for partners belonging to the same or different karyotypes or lineages, along with a white-tailed deer buck (Odocoileous virginianus) as an outgroup control. Behaviours were video recorded and analysed by using Generalized Linear Mixed Models, with the interacting females and males as random subjects. The results show that although red brocket females never accepted copulations with the control male, trials involving pairs of red brocket deer may or may not end with copulation regardless as to whether the partners belonged to the same or different lineages. Although some male and female behaviours differed when pairs belonged to the same or different lineages, our results do not support the existence of a precopulatory barrier between lineages in the red brocket deer complex. We discuss the implications for sympatric speciation and species conservation.
Keywords: Courtship behaviour; Cytotypes; Mate choice; Mating; Mazama americana; No-choice experiments; Premating barriers; Speciation